A study on Ombudsman as an alternative to Public Complaint Bureau (PCB) in Malaysia / Nur Atiqah Zayadi, Shafihani Md. Ali and Siti Solihah Ismail - Zayadi, Nur Atiqah; Md. Ali, Shafihani; Ismail, Siti Solihah (2011)
A Study on Ombudsman as an Alternative to Public Complaint Bureau (PCB) in Malaysia is a research paper focussing on the suitability of ombudsman to be practice in Malaysia. This research paper will touch on the weakness of PCB as an institution in handling the complaint lodged by the public towards the government. More importantly, the research paper will lay out the recommendations as to whether the ombudsman could be implemented in Malaysia by referring to the practice of ombudsman in United Kingdom, New Zealand and Mauritius. The research is set out systematically, firstly it deals with the historical background, the features and characteristics of PCB as well as their procedures on how complaints to be dealt with in Chapter Two. Secondly, in Chapter Three there will be comparison between the ombudsman process in United Kingdom, New Zealand and Mauritius in the aspects of history of development of ombudsman, legal powers, the procedure of ombudsman and nature of complaints. Thirdly, Chapter 4 deals with comparisons between PCB and the three ombudsmen which are United Kingdom, Mauritius and New Zealand. Finally, Chapter Five sets out the strength and weaknesses of PCB, recommendations and restriction in practicing ombudsman in Malaysia.